Teacher Induction Policy Development and Implementation: A Case of Ontario’s New Teacher Induction Program (NTIP) - Kutsyuruba, Benjamin; Godden, Lorraine; Walker, Keith (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2024)
Attrition and turnover among early career teachers (ECTs) have garnered the attention of policymakers and educational leaders across Canada. However, due to provincial/territorial responsibility for education in Canada, teacher induction efforts to keep novice teachers in the profession depend on school system structures and policies specific to given jurisdictions. This article describes an in-depth policy analysis of the development and implementation of Ontario’s New Teacher Induction Program (NTIP). Using a policy document analysis methodology, the review of the induction policy mandates, program evaluations, and empirical studies highlights the NTIP’s organization and scope, the stakeholders’ roles, duties, and responsibilities, the programmatic impacts, and the challenges associated with its implementation. The article concludes with implications for policy development and implementation as well as for the practice of supporting ECTs.